Plasma total homocysteine and macrovascular complications are associated with food and nutrient intake in patients with Type II diabetes mellitus - Chang, Namsoo (The Korean Nutrition Society and The Korean Society of Community Nutrition, 2007)
The present study was conducted to document the association between plasma homocysteine levels and the presence of macrovascular angiopathy with food and nutrient intake patterns among patients with Type II diabetes mellitus in Korea. Plasma total homocysteine concentration was analyzed by HPLC-fluorescence detector method in 127 patients with non-insulin dependent diabetes mellitus. Logistic regression analyses were performed respectively to study the association of plasma homocysteine levels with clinical and dietary characteristics and macroangiopathy (MA). The average plasma homocysteine level of patients with MA was 14.2 µmol/l, which was significantly higher than that of patients without MA (11.4 µmol/l). The proportions of patients with MA showed a significant difference, being 32.3% in hyperhomocysteinemic (>14.0 µmol/l) patients and 13.5% in others with homocysteine levels lower than 14.0 µmol/l. Odds ratios for macroangiopathy by tertile increase of plasma homocysteine concentration were 1.633 (Q(2)) and 4.831 (Q(3)), when adjusted for age, sex, and cigarette smoking. Patients with MA consumed reduced amounts of vitamin B(1), B(2), and folate. The results indicate that the plasma homocysteine levels are significantly increased in NIDDM patients who have macroangiopathy. Dietary management such as increased fruits and vegetables and decreased potatoes and starches might be beneficial for the prevention of macroangiopathy in diabetic patients.